Percepções dos gestores organizacionais acerca do investimento realizado na qualificação de seus colaboradores no mestrado profissional em administração e controladoria - Miranda, Vânia Odete Abreu de (2012)
The professional education develops training with a focus on practical preparation observing the work environment which has attracted growing interest of organizations, a fact evidenced by the constant presence of this theme in the media specialized in training courses and scientific publications. From the a theoretical study that addresses this thematic, this study investigates the opinions of organizational managers in the results of the investment made for the qualification of its employees in the professional master's degree, since they are primarily responsible for the decision to invest in human capital. Therefore key elements for understanding the issues considered essential when it brings to discussion aspects even without formal registration, perceived in organizations regarding to expectations and observed results about the learning aspects of employees. In order to reach the main purpose of this study, a qualitative methodology and descriptive with techniques of bibliographical research and field observation were used, with a case study in the Professional Master in Management and Controllership (MPAC) of Federal University of Ceará (UFC). For data collection, interviews were conducted with organizational managers, in which eleven companies were selected since they invested in training programs of at least three employees, from 2003 to 2009. Therefore, it was also analyzed the trajectory of graduates whose data were provided by the Coordination of MPAC. The results show a significant number of graduates in leadership positions, whichever is the incentive for completion of the professional master's degree as a strategy for training and development for organizations, with strong demand on the training for teachers. Regarding the trajectory of graduates, the data show that the majority of respondents are from private organizations and have more occupational mobility among three options (non-teaching employees, entrepreneurs and teachers), but most continued on home organization. Have the views of managers, principal axis analysis of this research, emphasize that the professional master's degree provides a favorable environment for the development of the organization and its employees, contributing to its growth. Regarding the MPAC, considered the training received important for the performance of activities and recommend to other establishments. Through these results, and in response to the problem guiding this research, it is concluded that the evaluation of managers, employees become more productive, allowing for benefits for themselves and for the organization.